SEMANTIC FEATURES OF TONGUE TWISTERS FORMED ON THE RAIN LEXICON IN UZBEK AND ENGLISH LANGUAGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the semantic characteristics of tongue twisters constructed on the basis of the rain lexicon in Uzbek and English languages. By analyzing lexical-semantic fields, metaphorical extensions, phonetic patterns, and cultural connotations, the study reveals how weather-related vocabulary—specifically lexemes denoting rain—functions within tongue twisters. A contrastive analysis demonstrates similarities in alliteration, onomatopoeia, and sound symbolism, as well as unique cultural elements present in each language. The findings highlight how rain-related lexemes enrich the expressive, phonetic, and cognitive dimensions of tongue twisters.